(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The author investigates the syntactic structure of various levels of difficulty, which are used in the interpersonal conflict communication. In this paper, considerable attention is paid to the analysis of the correlation of these structures with certain stages of the passage of the conflict. The idea substantiates that opponents consciously elect conflict syntactic markers at a certain stage of the conflict, those markers affect the entire system of communication and mechanisms for its deployment, depending on behaviour model, strategy and tactics of the opponent.